Implementation of a youth-adult partnership in Malaysian university-community collaborative: managing multiple hierarchies for youth development - Arokiasamy, Eugene Fransua; Krauss, Steven Eric (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This paper focuses on a youth-adult partnership(Y-AP) based university-community collaborative called the Books for Peace Initiative 2017-2020. The article describes the development, implementation challenges and success of Y-AP-based not-for-profit, university community collaboration in Malaysia. Grounded in bioecological theory and development relationships as a key medium of facilitation for positive youth development with Y-AP as the recognised practice for implementation, achieving the project objectives. Although much of the previous research on Y-AP is qualitative in nature, case studies continue to be effective way of building a cross-cultural knowledge base point to different ways that Y-AP can be used to develop young people and build effective youth-adult collaboration. This paper reports on a Y-AP university-community collaborative involving youth aged 20-25. Specifically we set out to describe the implementation of Y-AP in a non-Western setting. The case study focuses on the description of as well as strategies for overcoming three types of hierarchical barriers common within large, bureaucratic institutions in non-Western settings. Youth and Adult relational culture as well as the bureaucratic culture of the public university setting are dealt with and discusses. It is an inductive study which will include both qualitative and quantitatively based data, is envisaged to produce research findings that may lead to unique grounded theoretical perspectives from an Asian viewpoint. It also compares this Asian viewpoint with the Western viewpoint, which includes differing power-distance relationships, and levels of agency and empowerment of both youth and adults.